Jenny Lisshammar - Thesis submitted in partial fulfilment of the degree of Doctor of Clinical Psychology (DClinPsych) - Lisshammar, JEL (2023)
A Systematic Review of the Research Literature 1. Identified Risks of Retraumatisation in, and Trauma-informed Adaptations to, Routine Secondary Gynaecological Care for Adult Women who have Experienced Sexual Violence: A Narrative Synthesis